Informed consent in psychotherapy: a survey on attitudes among psychotherapists in Switzerland - Klara Eberle; Martin grosse Holtforth; Marc Inderbinen; Jens Gaab; Yvonne Nestoriuc; Manuel Trachsel (BMC Medical Ethics, 2021)
Abstract Background The legal and ethical guidelines of psychological professional associations stipulate that informed consent by patients is an essential prerequisite for psychotherapy. Despite this awareness of the importance of informed consent, there is little empirical evidence on what psychotherapists’ attitudes towards informed consent are and how informed consent is implemented in psychotherapeutic practice. Methods 155 psychotherapists in Switzerland completed an online survey assessing their attitudes regarding informed consent. Results Among the surveyed psychotherapists, there was a high consensus on important information that should be communicated to patients in the context of informed consent. Almost all psychotherapists rated confidentiality and its exemptions (95%) and self-determined decision-making (97%) as important. The importance to disclose information regarding fees and the empirical effectiveness of the provided treatment, were both seen as important by more than 80% of participants. The disclosure of personal information about the therapist was rated as important by 60%. Other aspects, which are not direct components of informed consent but rather overarching goals, were also evaluated rather homogeneously: self-determined decision making of the patient was rated as important by almost all of the surveyed psychotherapists (97%). The following components were also judged as important by a majority of the participants: promotion of hope (80%) and discussion of treatment goals (93%). Most psychotherapists described the implementation of informed consent as an ongoing process, rather than a one-time event during the first session of therapy. Therapists’ age, postgraduate training, treated patient group, and setting influenced attitudes towards informed consent. Conclusions The present study shows that informed consent is perceived by psychotherapists as both a challenge and a resource. The implementation of informed consent in psychotherapy requires further research from a clinical and ethical perspective.